The Association between Hepcidin and Iron Status in Children and Adolescents with Obesity - Ekkarit Panichsillaphakit; Orapa Suteerojntrakool; Chitsanu Pancharoen; Issarang Nuchprayoon; Sirinuch Chomtho (Journal of Nutrition and Metabolism)
Introduction. Iron deficiency (ID) is the most common nutritional deficiency found in pediatric practice. A higher prevalence of ID may be found in children with obesity. Obesity is a chronic low-grade inflammatory condition. It is postulated that inflammation increases hepcidin, a regulator of iron homeostasis. The aim of this study was to investigate the associations between iron status, hepcidin, and BMI-standard deviation score (BMI-SDS) in children with and without obesity. Methods. A cross-sectional study of Thai children with obesity (5 to 15 years old) versus age- and sex-matched, nonobese controls was conducted. A total of 63 children with obesity and 27 controls were enrolled. Complete blood count, serum iron, ferritin, transferrin saturation, and total iron binding capacity were analyzed. Serum hepcidin-25 was assayed using a hepcidin ELISA Kit (Human Hepc25). Results. There were 63 children with obesity, the median age (IQR) being 10 (9–13) years, and 27 controls. The median (IQR) BMI-SDS of the obese group was 2.3 (2.0–2.6) vs. −0.5 ((−1.3)−0.4) of the control group. ID was diagnosed in 27 children in the obese group (42.9%); 4 of the children with obesity and ID had anemia. Serum hepcidin-25 levels of the children with ID vs. without ID in the obese group were not significantly different (median (IQR) 25 (12.9–49.2) and 26.4 (12.6–43.6), respectively) but both of them were significantly higher than controls (19.7 (8.3–25.5) ng/ml, p = 0.04). BMI-SDS was positively correlated with hepcidin-25 (r = 0.28, p = 0.001). Conclusion. Prevalence of iron deficiency in Thai children with obesity and serum hepcidin-25 was higher than controls. Further study in a larger population, preferably with interventions such as weight loss program, is warranted to clarify this association.